Types and microbial genesis of carbonate microbodies in Zoophycos from the Pennsylvanian to Cisuralian Taiyuan Formation in North China - Hui-Bo Song; Xiang-Yu Zhang; Shun-Xi Liu; Bin Hu; Rui-Rui Guo; Yu-Jun Bi (Journal of Palaeogeography, 2018)
Abstract Many kinds of ichnofossil Zoophycos occur commonly in the carbonate rocks of Pennsylvanian to Cisuralian Taiyuan Formation in North China. In this study, carbonate microbodies types were identified in four differently-colored fillings of Zoophycos using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Based on the morphologic characteristics, these carbonate microbodies can be divided into three groups, i.e., spheroids, framboids and rhabditiforms. According to the structural features of surface and individual or aggregate morphologies, the three groups can be further subdivided into thirteen types: (1) smooth spheroids; (2) spheroids with tiny thorns; (3) spheroids with a finely granulated surface; (4) spheroids with a flocculent surface; (5) spheroids with a vermiform surface; (6) framboid monomers; (7) framboid colonies; (8) linear smooth rhabditiform bodies; (9) smooth rhabditiform bodies with expanding ends; (10) biserial rhabditiform bodies; (11) spiral rhabditiform bodies; (12) thorny rhabditiform bodies; and (13) branched rhabditiform bodies. This paper not only describes the morphology, composition and occurrence of the various carbonate microbodies, but also discusses their possible microbial genesis, as follows: (1) carbonate spherical microbodies most likely were generated after globular bacterial cells had been fully displaced by minerals; (2) framboid monomers and colonies corresponding to the morphology of biogenic strawberry (or raspberry) pyrite, with their appearance and internal structure possibly inheriting the morphology of microbial cells, were indirectly generated by some microenvironmental changes due to microbial activity; (3) the morphological features, size, occurrences and preservation of filamentous and rhabditiform microbodies indicate that they may be biogenic structures, and possibly mineralized microbial fossils; and (4) some kind of symbiotic relationship exists between microbial action and the Zoophycos trace-makers. Besides, the differently-colored fillings of Zoophycos are most likely closely related to differences in the composition of microbial taxa, which in turn reflect different microenvironmental conditions.